Evaluation of the Seismic Performance of The X Building Structure in West Jakarta Using Nonlinear Pushover Static Analysis - Faradhilla, Nafisha; Erizal; Sekar Mentari (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
Jakarta, which is close to the earthquake path, has a high potential for seismic hazards, so building structures must be designed to withstand earthquakes. The X Building, located in West Jakarta, is expected to have an earthquake-resistant structure, evaluated using pushover analysis. This study aims to assess the performance of the X Building structure against earthquake loads using pushover analysis with ETAS software. X Building underwent translation in patterns 1 and 2, followed by rotation in pattern 3. The value of the structure period in the X direction is 2.578 seconds, and in the Y direction is 2.252 seconds. The mass participation requirement has been met, with a participation rate of 90% or higher in all three directions. There is torsional irregularity in the Y direction. The dynamic shear force after scaling is 10,503.93 kN (X) and 10,503.94 kN (Y). When the performance point is reached, the roof displacement is 623.182 mm (X) and 513.267 mm (Y). The total number of plastic hinges is 2774 in the X direction and 2330 in the Y direction. The structural performance level obtained is Damage Control (DC). The ductility value in the X direction is 1.31, and in the Y direction is 1.12.